2020
DOI: 10.1111/dth.13584
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reliability and validity of the Patient Health Questionnaire‐9 in patients with acne

Abstract: To evaluate the reliability and validity of the Patient Health Questionnaire‐9 (PHQ‐9) in patients with acne. Three hundred acne patients were enrolled from January 2019 to December 2019. PHQ‐9 and Hamilton Depression Scale(HAMD) survey was conducted to evaluate their depression status. Cronbach's α coefficient and test‐retest reliability after 1 week were used to analyze the reliability of PHQ‐9. Factor analysis, Spearman correlation analysis, receiver operating characteristic curve (ROC curve) were used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The PHQ-9 is a nine-question instrument originally given to patients in a primary care setting to screen for the presence and severity of depression; it is widely adopted to test mental health wellbeing [ 31 , 32 , 33 ] and is suitable for use for patients of various cultural backgrounds [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. In the general Chinese population, the Chinese version of the PHQ-9 is a valid tool with good reliability for screening depression [ 43 , 44 , 45 ], and it is widely used in the populations of China, Hong Kong, and Taiwan [ 46 , 47 , 48 ]. The items of PHQ-9 are the following: Q1: Little interest or pleasure in doing things?…”
Section: Methodsmentioning
confidence: 99%
“…The PHQ-9 is a nine-question instrument originally given to patients in a primary care setting to screen for the presence and severity of depression; it is widely adopted to test mental health wellbeing [ 31 , 32 , 33 ] and is suitable for use for patients of various cultural backgrounds [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. In the general Chinese population, the Chinese version of the PHQ-9 is a valid tool with good reliability for screening depression [ 43 , 44 , 45 ], and it is widely used in the populations of China, Hong Kong, and Taiwan [ 46 , 47 , 48 ]. The items of PHQ-9 are the following: Q1: Little interest or pleasure in doing things?…”
Section: Methodsmentioning
confidence: 99%
“…The performance of this tool demonstrated good discrimination and calibration assessed by AUC, and it was of great value for accurate assessment of the risk of UEE. The AUC of the tool was 0.89, which was close to 0.9, indicating that the diagnostic accuracy was high (Peng et al, 2020). In this study, the best cut-off value to detect UEE risk in patients with artificial airway appears to be 15, which had a PPV of 42.86% and a NPV of 96.50%.…”
Section: Discussionmentioning
confidence: 82%
“…Five studies preset a cutoff value and calculated the Chinese language PHQ-9 sensitivity/specificity using that cutoff value—two studies chose 10 as the cutoff, 37 , 39 two studies chose 15, 25 , 38 and one study chose 9. 45 Studies that did not use a preset cutoff value and conducted receiver operating characteristic (ROC) curve analyses found that the area under the ROC curve ranged from 0.78 to 0.977. These studies identified ideal cutoff values ranging from 6 to 11, with 10 being the most common (6/15 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies additionally analyzed the test/retest reliability for the Chinese language PHQ-9. Of these, four retested their patients after an interval of 1 week, resulting in coefficients ranging from 0.824 to 0.955 38 , 44 , 45 ; five retested their patients after 2 weeks, resulting in coefficients ranging from 0.70 to 0.87 41 , 42 , 46 , 48 , 49 ; and one study retested their patients after 4 weeks, resulting in a coefficient of 0.873. 50 …”
Section: Resultsmentioning
confidence: 99%